SCN1A exon 26 variants in epilepsy and migraine patients - Nova Dian Lestari; Endang Mutiawati; Ahmad Hamim Sadewa; Hasan Sjahrir; . Syahrul; Dessy Rakhmawati Emril; . Harapan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Epilepsy and migraine are common neurological diseases in many populations. Mutation of the voltage gated natrium channel Nav1.1 (SCN1A) are important causes of different genetic epilepsies and can also cause familial hemiplegic migraine (FHM-III). This study aimed to identify SCN1A gene variation in patients with epilepsy and common migraine. Gene variation analysis of exon 26 of the SCN1A gene was carried out in 33 patients with epilepsy, 33 patients with migraine and 30 control individuals from Neurology Polyclinic at Dr. Zainoel Abidin General Hospital, Banda Aceh. The PCR and direct sequencing methods were performed in this study. SCN1A gene variations were identified in two epilepsy patients. These gene variations located at exon 26 were four silent mutations in patient E27 at position A4440T (Leu1480Leu), T4443C (Leu1481Leu), A5046G (Leu1682Leu) and C5121T (Asp1707Asp). One silent mutation in patient E30 at position G5505A (Glu1835Glu). None of these gene variations were identified in controls and patients with common migraine in this study. This study has identified 5 genetic variations of SCN1A in patients with epilepsy but not in common migraine. The mechanism and relationship between these variants and epilepsy need to be clarified.